PHYTOTOXICITY OF PENDIMETHALIN IN MUSTARD AND EFFECT OF WEED CONTROL ON PLANT NUTRIENTS’ CONSERVATION IN SOIL - SARKAR, A.; MUKHERJEE, P.K. (Annals of Agricultural Research, 2014)
Results obtained in the experiment showed that pendimethalin had higher weed control efficiency than fluchloralin, however, pendimethalin became phytotoxic to mustard and non-selective in action at all the doses. Among the herbicides fluchloralin 1.25 kg a.i. ha-1 registered highest seed yield of mustard (10.39 q. ha-1) as it controlled the weeds like Polygonum percsicaria, Polygonum pensylvanicum, Polygonum orientale and Stellaria midia effectively. However, black necrotic symptom at the base of the plant was observed during siliqua development stage, which disappeared at later part of crop growth. Weeds removed huge amount of plant nutrients from soil to the tune of 165.13 kg N, 22.54 kg P and 158.84 kg K ha-1. Fluchloralin at 1.00 kg a.i. ha-1 was effective as preemergence herbicide in mustard to control weeds and to conserve the plant nutrients in soil on account of 118.08 kg N, 15.56 kg P and 104.58 kg K ha-1.